Initial expression levels of nimA are decisive for protection against metronidazole in Bacteroides fragilis. (October 2022) - Kupc, Małgorzata; Paunkov, Ana; Strasser, Doris; Sóki, József; Leitsch, David
Abstract: Objectives: In the genus Bacteroides, the nim genes are resistance determinants for metronidazole, a nitroimidazole drug widely used against anaerobic pathogens. The Nim proteins are considered to act as nitroreductases. However, data from several studies suggest that the expression levels of Nim do not increase with increasing resistance which is conflicting with this notion. The impact of Nim protein levels on low-level metronidazole resistance, however, representing the early stage of induced resistance in the laboratory, has not been assessed as yet. Methods: The nimA gene was cloned into two different plasmids and introduced into B . fragilis strain 638R. Expression levels of nimA mRNA were measured by RT-qPCR and compared to those in strain 638R harbouring plasmid pI417, the original clinical plasmid harbouring IS element IS 1168 with the nimA gene. Further, metronidazole susceptibility was assessed by Etest and the activity of pyruvate:ferredoxin oxidoreductase (PFOR) was measured in all strains after induction of high-level metronidazole resistance. Results: The level of protection against metronidazole by nimA correleated with the level of expression of nimA mRNA. Further, the activity of PFOR in highly-resistant B . fragilis 638R was only preserved when expression levels of nimA were high. Conclusions: Although the development of high-level metronidazole resistance in B . fragilis strains with a nimA gene is not caused by an increase of nimA expression as compared to the less resistant parent strains, nimA expression levels might be of decisive importance in the early stage of resistance development. This has potential implications for metronidazole resistance in clinical isolates. Highlights: Expression level of nimA in B. fragilis depends on the promoter. Initial protection from metronidazole by NimA depends on the expression level. Enhancement of PFOR activity by NimA also depends on the expression level.